IMPLICIT MEANING OF WORDS IN COMMUNICATION: A PRAGMATIC ANALYSIS (SCIENCE TIME JOURNAL, 2026)
This article examines the implicit meaning of words in communication from a pragmatic perspective. The study focuses on how speakers convey meanings indirectly through conversational implicatures, presuppositions, and contextual inferences. A qualitative descriptive method was employe to analyze examples from English discourse. The findings reveal that implicit meaning plays a significant role in effective communication by facilitating politeness, communicative efficiency, and social interaction. The research highlights the importance of pragmatic competence in understanding hidden meanings and improving language proficiency.